Pemberdayaan Kader Kesehatan pada Psikoedukasi Keluarga Menurunkan Beban Subjektif Keluarga Gangguan Jiwa - Maria Theresia Monica Elsina; Budi Anna Keliat; Ice Yulia Wardani; Herni Susanti; Novy Helena C. Daulima (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to determine the effect of burden management using the approach of health cadres and community leaders through family psychoeducation in overcoming the subjective burden of families in caring for clients with mental disorders. The method used is a case report. This case report was carried out on a family with a family member with mental illness. The intervention given to the family was family psychoeducation, which was carried out in 6 sessions involving health cadres and community leaders. The research results show that burden management sessions in family psychoeducation involving the role of cadres and community leaders can reduce the family's burden. In conclusion, family burden management involving health cadres and community leaders can reduce the subjective responsibility of families in caring for clients with mental disorders. Keywords: Family burden, Health Cadres, Family Psychoeducation